The impacts of shipping and related activities on ocean sustainability : a study into the various aspects to overcome global impacts in the context of shipping - Huang, Zhiwei (Nanyang Technological University, 2021)
In the pursuit of a sustainable economy, various environmental issues have been brought about for discussions. In the maritime sector, the topic of Ocean sustainability has been floating about since early 1970s. As the industry relies heavily on the Ocean to survive, it is of crucial importance that the industry plays its part in ensuring the wellbeing of the Ocean. As a primary user of the Ocean, shipping, and its activities have undoubtedly impacted the Ocean significantly in many ways. Being an international business, the maritime industry is heavy regulated by International Maritime organisation (IMO). IMO consistently seeks out weak linkages amongst the industry and seek to enforce regulations and introduce conventions to minimize the impacts of the industry on the Ocean. Couple with national and organisational efforts, IMO seeks to ensure that sustainable shipping is achieved at minimal expense to Ocean’s health. The paper seeks to identify the impacts of shipping and its related activities on ocean sustainability. It will also analyse current regulations and initiatives and evaluate their effectiveness. The paper will be focused primarily on regulations regarding shipping activities. Some proposals to reduce the impacts of the industry and improve the effectiveness of current regulations will also be discussed under recommendations. This paper uses primarily interview responses from industry professionals and past studies on this topic to derive a meaningful and well – balanced research paper.